A CLINICOPATHOLOGICAL STUDY OF SUBACUTE INTESTINAL OBSTRUCTION WITH SPECIAL EMPHASIS ON THE ROLE OF LAPAROSCOPY IN DIAGNOSIS (Asian Journal of Medical Research and Health Sciences, 2026)
Introduction: The term "intestinal obstruction" refers to the impairment of the normal transit of intestinal contents, which can be caused by a lesion or, in the absence of one, by a mechanical obstruction or a lack of normal intestinal motility. Aims: Analysis of clinical, investigative and pathologic data to arrive at the diagnosis of subacute intestinal obstruction, its etiologic causes and to figure out the role of diagnostic laparoscopy in its evaluation. Materials & Methods: Study design was Prospective Study, from January 2021 to June 2022, total sample size 40 and Study area were Department of General Surgery, CNMC&H, Kolkata Result: 6 (37.5%) patients in our study underwent appendectomy; 2 (12.5%) underwent Cholecystectomy; 5 (31.2%) underwent gynecological; and 3 (18.8%) underwent exploratory laparotomy. Nan is the value of z. P has a value of less than.00001. At p